2010
DOI: 10.1177/197140091002300507
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Choroid Plexus in Neurotuberculosis: MR Findings in Six Cases

Abstract: The majority of intracranial infections that cause meningitis are considered to start in the choroid plexus of the ventricles, but lesions involving the choroid plexus are rare. There are isolated case reports of the involvement of choroid plexus in tuberculous meningitis. The main imaging findings are abnormal enhancement of the thickened choroid plexus, asymmetric hydrocephalus with sequestrated temporal horn, periventricular edema and intraventricular septae formation. Six patients having tubercular involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Adhesions formed between the inflammed ependyma and choroid plexus results in intraventricular septations, ventricular sequestrations, and there by, transependymal seepage of CSF due to obstructed CSF flow. 10,11 Irrespective of the underlying cause, most common MRI finding in ventriculitis is the presence of intraventricular debris and pus on diffusion and FLAIR imaging. Abnormal periventricular and subependymal hyperintensity with enhancement of ventricular wall are the hallmark imaging features; while choroid plexitis is seen as enlarged poorly marginated intensely enhancing choroid plexus on contrast administration.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesions formed between the inflammed ependyma and choroid plexus results in intraventricular septations, ventricular sequestrations, and there by, transependymal seepage of CSF due to obstructed CSF flow. 10,11 Irrespective of the underlying cause, most common MRI finding in ventriculitis is the presence of intraventricular debris and pus on diffusion and FLAIR imaging. Abnormal periventricular and subependymal hyperintensity with enhancement of ventricular wall are the hallmark imaging features; while choroid plexitis is seen as enlarged poorly marginated intensely enhancing choroid plexus on contrast administration.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculomas with solid central caseation appear as hypo-to isointense on both T1 and T2 weighted images with iso-to hyperintense rim on T2WI and peripheral rim-like post-contrast enhancement. On the other hand, intracranial tuberculomas with central liquefaction appear hypointense on T1WI and hyperintense on T2WI with peripheral hypointense rim which shows irregular rim-like peripheral enhancement on the post-contrast study [6,9,12,14,17,18]. Central region of T2 hypointensity is a valuable finding in tuberculoma as it is not found in several other space-occupying lesions [19].In our series, 12 patients (54.5%)of giant tuberculoma demonstrated a central region of T2 hypointensity.…”
Section: Discussionmentioning
confidence: 99%
“…Disorders in which ChP volumetric changes have been described span from psychiatric (autism spectrum disorder, psychosis, depression) [18–20] to neurodegenerative (Alzheimer's, Parkinson's) [21,22] and infectious (e.g. CNS cryptococcosis, neurotuberculosis) diseases [23,24]. In the last couple of years, converging results from independent research groups have further demonstrated that ChPs are enlarged in PwMS compared with healthy controls [16 ▪▪ ,25 ▪ ,26 ▪▪ ,27 ▪ ], raising interest on these structures as potential novel MRI biomarker of neuroinflammation [28].…”
Section: In Vivo Analysis Of Choroid Plexuses In Human: the Imaging T...mentioning
confidence: 99%